2016
DOI: 10.1039/c6tb01827k
|View full text |Cite
|
Sign up to set email alerts
|

Human serum albumin encapsulated gold nanoclusters: effects of cluster synthesis on natural protein characteristics

Abstract: This version is available at https://strathprints.strath.ac.uk/58002/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…This large increase coincides with a change in colour from clear to cloudy and also matches the pH range at which aggregation of Ly-AuNCs was seen from DLS experiments, confirming the previous result. This result agrees well with the pH induced aggregation of HSA-AuNCs previously reported 32 .The electrophoretic mobility of both Lysozyme and Ly-AuNCs was measured across a pH range of 3-11, at a concentration of 1000 ppm in both cases. The associated zeta potentials were calculated using Henry's equation, [3], and displayed in Figure 3.…”
Section: Resultssupporting
confidence: 91%
“…This large increase coincides with a change in colour from clear to cloudy and also matches the pH range at which aggregation of Ly-AuNCs was seen from DLS experiments, confirming the previous result. This result agrees well with the pH induced aggregation of HSA-AuNCs previously reported 32 .The electrophoretic mobility of both Lysozyme and Ly-AuNCs was measured across a pH range of 3-11, at a concentration of 1000 ppm in both cases. The associated zeta potentials were calculated using Henry's equation, [3], and displayed in Figure 3.…”
Section: Resultssupporting
confidence: 91%
“…For further confirmation of structural assemblies of CuNCs‐HSA complex, we performed dynamic light scattering (DLS) experiments with different concentration of HSA (ranging from 0–400 μM). The hydrodynamic diameters of CuNCs and HSA alone were found to be ∼1.9 nm and ∼8.1 nm, respectively which are in agreement to the previously reported values ,. Hydrodynamic diameter of CuNCs‐HSA assembly gradually increases with increasing concentration of HSA and finally reaches to ∼10.2 nm in presence of 400 μM HSA (Figure S4).…”
Section: Resultssupporting
confidence: 91%
“…The hydrodynamic diameters of CuNCs and HSA alone were found to be~1.9 nm and~8.1 nm, respectively which are in agreement to the previously reported values. [12,33] Hydrodynamic diameter of CuNCs-HSA assembly gradually increases with increasing concentration of HSA and finally reaches tõ 10.2 nm in presence of 400 mM HSA ( Figure S4). This data very well corroborates with our FCS measurements and establishes a monolayer coverage of HSA atop the NC surfaces.…”
Section: Fluorescence Correlation Spectroscopymentioning
confidence: 97%
“…Glutathione has been extensively used for AuNC synthesis due to the strong affinity of the thiol group to form AuS bond . Cysteine‐containing proteins such as bovine serum albumin, insulin, trypsin, and lysozyme have been also explored for the same purpose. Other studies have also shown that basic amino acids together with tyrosine and tryptophan can contribute to the reduction of the ions to metallic gold .…”
Section: Introductionmentioning
confidence: 99%